Implementation of structured trauma training for first-year surgical residents in Ethiopia: a novel pilot program in a low income country - Segni Kejela; Meklit Solomon Gebremariam (Journal of Trauma and Injury)
Purpose Curricula for surgical residents should include training in trauma care; however, such training is absent in many low income countries. At the largest surgical training institution in Ethiopia, a trauma training program was developed, integrated into the existing surgical curriculum, and implemented. This study was conducted to evaluate the trainees’ response to the new program. Methods Over a 5-month period, 35 first-year surgical residents participated in weekly trauma care training sessions. The program included journal clubs, practical sessions, didactic sessions, and case-based discussions. Six months after the conclusion of the training, changes in knowledge, attitude, and practices were evaluated through a self-report survey. Results For knowledge-based items, the survey data revealed reported improvements in 83.8% to 96.8% of students. Furthermore, 90.3% to 93.5% of participants indicated improvements in practice, while 96.7% exhibited a change in attitude. Respondents reported that attending didactic courses improved their presentation skills and facilitated the acquisition of knowledge. They suggested the inclusion of additional practical sessions. Conclusions Training structures that are simple to implement are crucial for residency programs with limited resources. Such programs can be developed using existing academic staff and can aid residents in delivering improved care to trauma patients.